Recommendations for influenza and Streptococcus pneumoniae vaccination in elderly people in China - Qiong Chen; Lijing Wang; Mingxuan Xie; Xiaoying Li; Recommendations for Influenza, Streptococcus pneumoniae Vaccination in Elderly People in China Writing Group, Geriatric Respiratory Group and Chinese Society of Geriatrics (Aging Medicine, 2020)
Abstract Influenza and pneumonia can be prevented by vaccination, but they remain major causes of morbidity and mortality in age‐related diseases. In most areas of China, the rates of influenza and pneumococcal vaccination are relatively low and public awareness of vaccination remains insufficient. Thus, it is essential to recommend influenza and Streptococcus pneumoniae vaccination to elderly people in clinical practice. Based on recently published studies and related documents issued by several vaccination authorities, such as the World Health Organization, the National Health and Wellness Committee, the Chinese Center for Disease Control and Prevention, the US Centers for Disease Control and Prevention, and the US Advisory Committee on Immunization Practices, we propose official recommendations for influenza and S pneumoniae vaccination in elderly people in China.